1996
DOI: 10.1088/0022-3727/29/11/020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of collisions on near-steady rotation in a vacuum arc centrifuge

Abstract: A two-dimensional fluid simulation of the plasma column present in a vacuum arc centrifuge after the anode grid has been developed. The simulation accounts for the effect of collisions on the plasma column, which is assumed to consist of multiply charged ions and electrons. It is found that the radial outwards plasma drift associated with collisions produces a spreading of the column density profile. With the plasma assumed to be in electrical contact with the anode grid, this in turn leads to a flow of curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…The first new result with respect to the collisionless case is the occurrence of a radial velocity v r in addition to the azimuthal one v h . Integrating the previous relations Equations (32) and (33) with respect to the radius gives the ions and electrons azimuthal v h and radial v r velocities: v he ¼ X e r; v hi ¼ X i r and v re ¼ X e r=a e , v ri ¼ X i r=a i . To express the angular velocities X i and X e as a function of the plasma parameters, we consider Eq.…”
Section: Collisional Slow Mode Decelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first new result with respect to the collisionless case is the occurrence of a radial velocity v r in addition to the azimuthal one v h . Integrating the previous relations Equations (32) and (33) with respect to the radius gives the ions and electrons azimuthal v h and radial v r velocities: v he ¼ X e r; v hi ¼ X i r and v re ¼ X e r=a e , v ri ¼ X i r=a i . To express the angular velocities X i and X e as a function of the plasma parameters, we consider Eq.…”
Section: Collisional Slow Mode Decelerationmentioning
confidence: 99%
“…where we have used the previous definition of the free energy parameter x Ã2 integrated with respect to the radius: ÀMx Ã2 r ¼ @[e/ þ k B Tlnðn=n 0 Þ]=@r. The relations equations (37) and (38) describe the impact of collisions on the azimuthal motion. The radial dynamics for collisional rigid body rotations can be described through the integration of relation equation (33) with respect to the radius. The radial flux of particles associated with collisional rigid body rotations for electrons C en and ions C in is C en ¼ n e X Àe a Àe r ¼ n e X Àe x e À 2X Àe e r;…”
Section: Rotation Induced Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hall parameter, ␤ϭ/v ie , is of order 100 in a typical vacuum arc centrifuge, and for this reason electron-ion collisions have been neglected in earlier works. 10 Recently Yue and Simpson 13 have shown that electron-ion collisions do have a small cumulative effect over the length of the rotation region in a VAC. For typical conditions, they predicted theoretically that the resultant plasma column expansion would lead to a reduction in the central ion density of less than 10% over the length of the VAC.…”
Section: Plasma Fluid Modelmentioning
confidence: 99%
“…In 1995, Simpson et al 5 showed experimentally and theoretically that the electrical conductivity of the anode grid creates a radial potential gradient that is responsible for azimuthal acceleration in the vacuum arc centrifuge. In 1996, Yue and Simpson 13 studied the effect of collisions on near-steady rotation in a vacuum arc centrifuge, showing that the effect of collisions on the plasma column after the anode grid is to increase the angular velocity, and possibly the separative performance of the plasma.…”
Section: Introductionmentioning
confidence: 99%